2016
DOI: 10.1124/mol.116.106369
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptor Endocytosis Confers Uniformity in Responses to Chemically Distinct Ligands

Abstract: The ability of chemically distinct ligands to produce different effects on the same G protein-coupled receptor (GPCR) has interesting therapeutic implications, but, if excessively propagated downstream, would introduce biologic noise compromising cognate ligand detection. We asked whether cells have the ability to limit the degree to which chemical diversity imposed at the ligand-GPCR interface is propagated to the downstream signal. We carried out an unbiased analysis of the integrated cellular response elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Primary cultures of human airway smooth muscle cells were established as described previously (Tsvetanova et al, 2016). Cells were passaged no more than 5 times using Trypsin-EDTA (Life Technologies) and maintained in 10% FBS in DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of human airway smooth muscle cells were established as described previously (Tsvetanova et al, 2016). Cells were passaged no more than 5 times using Trypsin-EDTA (Life Technologies) and maintained in 10% FBS in DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphoproteomics is an alternative approach to understand how GPCR activation changes kinase and phosphatase activity in the cell. One advantage to phosphoproteomics is that it can be used to detect and identify thousands of phosphosites; thus, examining GPCR activity from the “cellular perspective.” For example, GPCR activation is estimated to change 1–10% of all phosphorylation sites in the cell 46–49 . As a comparison, an estimated 16–20% of phosphosites can be regulated upon receptor tyrosine kinase (RTK) stimulation 50,51 …”
Section: A “Cellular Perspective” Of Gpcr Signaling: Phosphoproteomicmentioning
confidence: 99%
“…Before discussing examples in which biased agonists change the targets of GPCR signaling when compared to their unbiased counterparts, it is important to highlight an example demonstrating that this is not always the case. Tsvetanova et al compared the cellular phosphoproteome of HEK293 cells endogenously expressing β2‐adrenergic receptor (β2AR) when stimulated by the full agonist isoproterenol compared to a partial agonist with G protein bias, salmeterol 48,52,53 . The authors found that salmeterol induced changes in the same phosphorylation sites as isoproterenol and the only difference was that the changes were smaller in magnitude with salmeterol 48 .…”
Section: A “Cellular Perspective” Of Gpcr Signaling: Phosphoproteomicmentioning
confidence: 99%
“…Over the past decade an expanded view has taken hold, supported by accumulating in vitro evidence that GPCRs are conformationally flexible [1][2][3][4][5] and a confluence of cell biological and in vivo evidence supporting the existence of functionally selective agonist effects [6][7][8] . According to this still-evolving view, agonists have the potential to promote GPCRs to selectively recruit one transducer or regulator protein over another, introducing bias into the signaling cascade at a receptor-proximal level that is either propagated downstream or eliminated during intermediate transduction steps 9,10 .…”
Section: Introductionmentioning
confidence: 99%